2006
DOI: 10.1086/508739
|View full text |Cite
|
Sign up to set email alerts
|

Jet Breaks in Short Gamma‐Ray Bursts. I. The Uncollimated Afterglow of GRB 050724

Abstract: We report the results of the Chandra observations of the Swift-discovered short gamma-ray burst GRB 050724. Chandra observed this burst twice, about 2 days after the burst and a second time 3 weeks later. The first Chandra pointing occurred at the end of a strong late-time flare. About 150 photons were detected during this 49.3 ks observation in the 0.4Y10.0 keV range. The spectral fit is in good agreement with spectral analysis of earlier Swift XRT data. In the second Chandra pointing the afterglow was clearl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
124
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 45 publications
(97 reference statements)
20
124
1
Order By: Relevance
“…It has been suggested that low-luminosity LGRBs (e.g., GRB 980425, GRB 031203, and GRB 060218) have large, and perhaps nearly quasispherical, opening angles when compared to traditional LGRBs (Soderberg et al 2004b(Soderberg et al , 2006bLiang et al 2007). Similarly, of the three SGRBs with estimated opening angles, GRB 050709 and GRB 050724 have large measured angles, Θ ∼ 14 • ) and ∼25 • (Grupe et al 2006;Malesani et al 2007), respectively, while GRB 051221 has 4 • < Θ < 8 • Soderberg et al 2006a), which is more typical of traditional high E γ, ISO LGRB opening angles. Yet both long and short populations appear to largely fall on a simple log-linear relationship between afterglow intensity and gamma-ray luminosity over 6 orders of magnitude in energy.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It has been suggested that low-luminosity LGRBs (e.g., GRB 980425, GRB 031203, and GRB 060218) have large, and perhaps nearly quasispherical, opening angles when compared to traditional LGRBs (Soderberg et al 2004b(Soderberg et al , 2006bLiang et al 2007). Similarly, of the three SGRBs with estimated opening angles, GRB 050709 and GRB 050724 have large measured angles, Θ ∼ 14 • ) and ∼25 • (Grupe et al 2006;Malesani et al 2007), respectively, while GRB 051221 has 4 • < Θ < 8 • Soderberg et al 2006a), which is more typical of traditional high E γ, ISO LGRB opening angles. Yet both long and short populations appear to largely fall on a simple log-linear relationship between afterglow intensity and gamma-ray luminosity over 6 orders of magnitude in energy.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…One immediate advantage offered by GRBs is that their bright electromagnetic emission allows a precise localization of the source on the sky, pinpointing the source directionn and lifting some of the degeneracies which limit distance determination. The extent of collimation in short GRBs is not well known, although recent analyses suggest that there may be a rather wide range in jet collimation from burst to burst [24,25]. For bursts that arise from binary NS mergers, our theoretical expectation is that emission should be beamed preferentially along the orbital angular momentum axis, where baryon loading is minimized.…”
Section: Grbs Observed By Gw Networkmentioning
confidence: 94%
“…Swift and HETE-2 observations have provided evidence of clear similarities with the afterglows detected in the correspondence of long GRBs, because of the detection of X-ray and optical afterglows (Soderberg 2006;Grupe 2006;Berger 2007). Other similarities identified in the spectra for the initial stage of short and long GRBs and the presence, in some cases, of X-ray flares infers that a common mechanism operates during the first few seconds (Barthelmyet et al 2005;Coward, 2007).…”
Section: Introductionmentioning
confidence: 93%